2013
DOI: 10.2527/jas.2012-5818
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of nitrogen excretion by beef cattle: A meta-analysis1,2,3

Abstract: Reliable estimates of N excretion in the urine and feces of beef cattle are essential for developing cost-effective and environmentally sound nutrient management plans. A meta-analysis dataset was compiled that included data for starting live BW, DMI, N intake, dietary CP and RDP concentrations, urine N excretion, and feces N excretion. The data were taken from 12 individual feeding trials that included N balance data, and represented a total of 47 different dietary treatments and 255 animals. Correlation anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 40 publications
(49 reference statements)
8
42
2
6
Order By: Relevance
“…Predictions of N excretion proposed by Waldrip et al (2013) and Dong et al (2014), and used by BCNRM (2016), also showed a positive correlation between nitrogen intake and excretion. These authors observed better fit of the prediction equations using the N intake than the percentage of crude protein in the diet, and the same behavior was observed in the present database.…”
Section: No3mentioning
confidence: 77%
See 3 more Smart Citations
“…Predictions of N excretion proposed by Waldrip et al (2013) and Dong et al (2014), and used by BCNRM (2016), also showed a positive correlation between nitrogen intake and excretion. These authors observed better fit of the prediction equations using the N intake than the percentage of crude protein in the diet, and the same behavior was observed in the present database.…”
Section: No3mentioning
confidence: 77%
“…Prior to generating new equations for nitrogen and phosphorus excretion, prediction equations of nitrogen and phosphorus excreted (Geisert et al, 2010;Waldrip et al, 2013;Dong et al, 2014) as proposed by BCNRM (2016), were tested for appropriateness for these database. The tested equations are presented below.…”
Section: Equations Proposed By Bcnrm (2016) Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Titanium dioxide concentration was determined in samples of duodenal digesta and feces according Myers et al (2004) to determine intestinal and total solids flow. (Waldrip et al, 2013).…”
Section: Chemical Analysesmentioning
confidence: 99%